Weight status prior to-, during- and post-school closures in the COVID-19 pandemic: A school-based cohort study in children aged 6 to 9 years: Weight status and COVID-19 pandemic - L. Sofiati, Sandro; P. Guedes, Dartgnam; Santos, Leandro; A. C. Andraus, Rodrigo; S. Ribeiro, Alex (Manual Therapy, Posturology & Rehabilitation Journal, 2026)
Background: School closures during the COVID-19 pandemic increased children’s exposure to obesogenic behaviors, potentially affecting weight status. Objective: To report temporal trends in the weight status of children aged 6 to 9 years before, during, and after school closures in response to restrictions imposed by the COVID-19 pandemic, using a three-year school-based cohort design. Method: Weight status was analyzed using the body mass index and diagnostic criteria proposed by IOFT. Initial data collection took place in 2020 (pre-pandemic period), in 2021 and 2022 (pandemic period), and in 2023 (post-pandemic period), after the reopening of schools. Results: The data collected confirmed that restrictions imposed to mitigate the adverse impact of the COVID-19 pandemic, including the full or partial closure of schools, substantially increased children’s weight above what would be expected for their sex and age. After two years of the pandemic period, 16% of children identified in the pre-pandemic period as with normal weight migrated to overweight, while 23% with overweight became obese. Data collected during the post-pandemic period showed signs of a reduction in excess weight accumulated during the pandemic; however, the prevalence rates of overweight and obesity remained at 14% and 26%, respectively, which were higher than in the pre-pandemic period. Conclusion: The findings suggest that the harmful effects contributing to greater weight gain during the COVID-19 pandemic were not spontaneously reversed. Therefore, specific actions to combat overweight and obesity are essential to avoid present and future adverse consequences in children’s health.